Analisis Penggunaan Model Word Square untuk Memotivasi Belajar Siswa - Nunu Andriani; Mulyadi Mulyadi; Abd. Hakim Naba (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: Analysis of the Use of the Word Square Model to Motivate Student Learning During a Pandemic. This study aims to describe the use of the word square model in learning to motivate student learning during a pandemic. The type of research used is qualitative. The sample in this study was 30 grade III students of SD Negeri Daya I Kota Makassar. The data collection techniques used are interviews, observations, questionnaires and documentation. The data analysis techniques used are collecting data, reducing data, presenting data and drawing conclusions. The results of this study show that the use of the word square learning model can increase the learning motivation of grade III elementary school students from the observation that the level of motivating student learning of 53.3% is included in the good category. It is known that the use of the word square model in learning in motivating learning in the early days of the pandemic.